2014
DOI: 10.1038/jes.2014.2
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric particulate matter size distribution and concentration in West Virginia coal mining and non-mining areas

Abstract: People who live in Appalachian areas where coal mining is prominent have increased health problems compared with people in non-mining areas of Appalachia. Coal mines and related mining activities result in the production of atmospheric particulate matter (PM) that is associated with human health effects. There is a gap in research regarding particle size concentration and distribution to determine respiratory dose around coal mining and non-mining areas. Mass- and number-based size distributions were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 19 publications
4
49
0
1
Order By: Relevance
“…Health problems are also related to size and composition of trafficrelated PM with toxicological evidence 5 . Huge amounts of PM are generated in and around surface mining areas due to operational use of high-capacity machines [6][7][8] . The increasing use of motor vehicles in urban areas is also a major source of generation of PM emission 9,10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Health problems are also related to size and composition of trafficrelated PM with toxicological evidence 5 . Huge amounts of PM are generated in and around surface mining areas due to operational use of high-capacity machines [6][7][8] . The increasing use of motor vehicles in urban areas is also a major source of generation of PM emission 9,10 .…”
mentioning
confidence: 99%
“…However, detailed characterization of hydrothermal particles has only rarely been attempted 5 . Recently, hydrothermal plumes from unknown vent(s) were discovered near 340N Carlsberg Ridge 6 . In the present study we determine the morphological and geochemical nature of these plume particles.…”
mentioning
confidence: 99%
“…Coal mining in the Appalachian region is environmentally destructive and has created serious ecological harms to local environment including hydrological impacts (Vengosh et al 2013;Evans et al 2015), polluting of surrounding streams and groundwater (McAuley & Kazor 2006;Lindberg et al 2011), reduced air quality (Aneja, Isherwood & Morgan 2012;Kruth et al 2014) and drastic changes in the topography of the land (Wickham et al 2013;Ross, McGlynn & Bernhardt 2016 There is evidence that air pollution, particularly particulate matter, is associated with neurodegenerative-related diseases and mortality (Kettunen et al 2007;Block & Calderon-Garciduenas 2009;Levesque et al 2011 …”
Section: Discussionmentioning
confidence: 99%
“…Scholars find mountaintop removal (MTR)MTR coal mining to be highly destructive to the environment (Palmer et al 2010;Aneja, Isherwood & Morgan 2012;Vengosh et al 2013;Kruth et al 2014;Evans et al 2015) and is linked to negative health outcomes, including increased mortality rates and reduced self-rated health (Hitt & Hednryx 2010;Hendryx, Fedorko & Anesetti 2010;Zullig & Hendryx 2010;Zullig & Hendryx 2011). While acknowledging that the role of socioeconomic status on coal mining in the region remains important, socioeconomic status may not be the only mechanism through which coal mining affects the health and wellbeing of the Appalachian region.…”
Section: Natural Resource Curse and The Appalachian Regionmentioning
confidence: 99%
“…Conclusions in a subsequent study noted the strength of the association between PM10 levels and respiratory health outcomes was similar across all communities (Howel, Darnell, & Pless-Mulloli, 2001). Kurth et al (2014) assessed geochemical characteristics of PM around surface mining operations and found increased levels of aluminosilicates, which affect the respiratory system, and another study indicated higher inhaled deposited lung dose in surface mining areas (Kurth, McCawley, Hendryx, & Lusk, 2014). Likewise, Jones et al (2002) (Rout, Masto, Ram, George, & Padhy, 2013).…”
Section: Air and Air Qualitymentioning
confidence: 99%